Mems-based oscillators: a review - Karim, Jamilah; Alam, A. H. M. Zahirul; Nordin, Anis Nurashikin (IIUM Press, 2014)
This paper presents an overview of microelectromechanical (MEMS) based oscillators. The accuracy and stability of the reference frequency will normally limit the performance of most wireless communication systems. MEMS technology is the technology of choice due to its compatibility to silicon, leading to integration with circuits and lowering power consumption. MEMS based oscillators also provide the potential of a fully integrated transceiver. The most commonly used topology for MEMS based oscillators are pierce oscillator circuit topology and TIA circuit topology. Both topologies result in very competitive output in terms of phase noise and power consumption. They can be used for either higher or lower Rx. The major difference between both topologies is the number of transistors used. TIA circuit used more number of transistor compare to pierce circuit. Thus design complexity of the TIA is higher. Pierce circuit is simpler, provide straightforward biasing and easier to design. The highly integratable of MEMS-based oscillators have made them much needed in future multiband wireless system. So that future wireless systems are able to function globally without any problem.